Engels@200: Friedrich Engels and Digital Capitalism. How Relevant Are Engels’s Works 200 Years After His Birth? - Christian Fuchs (tripleC: Communication, Capitalism & Critique, 2020)
This paper takes Friedrich Engels 200th birthday on 28 November 2020 as occasion to ask: How relevant are Friedrich Engels’s works in the age of digital capitalism? It shows that Engels class-struggle oriented theory can and should inform 21st century social science and digital social research.